2004
DOI: 10.1111/j.1365-2249.2004.02588.x
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of IL-18 and predominance of a Th1 immune response is a hallmark of lupus nephritis

Abstract: SUMMARYThere is evidence that nephritis is dominated by a Th1 immune response in systemic lupus erythematosus. Since IL-18 promotes polarization of the immune response toward Th1, we investigated the role of this cytokine in lupus nephritis (LN). A total of 133 lupus patients and 44 healthy subjects were enrolled. Demographic and clinical characteristics with renal biopsy data were recorded. IL-18 along with IFN-g and IL-4, two prototypical of Th1 and Th2 cytokines, were measured in serum by ELISA. Peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
111
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(126 citation statements)
references
References 41 publications
15
111
0
Order By: Relevance
“…Previous findings supported the notion that Th1 cytokines could play an important role in inflammation and tissue injury and are correlated with the development of SLE and, in particular, lupus glomerulonephritis (43)(44)(45)(46). We detected IL-17ϩ T cells in MRL/lpr mouse kidneys (data not shown), but whether Th17 cells are implicated in these forms of SLE requires further investigation.…”
Section: Discussionsupporting
confidence: 66%
“…Previous findings supported the notion that Th1 cytokines could play an important role in inflammation and tissue injury and are correlated with the development of SLE and, in particular, lupus glomerulonephritis (43)(44)(45)(46). We detected IL-17ϩ T cells in MRL/lpr mouse kidneys (data not shown), but whether Th17 cells are implicated in these forms of SLE requires further investigation.…”
Section: Discussionsupporting
confidence: 66%
“…Other alterations include changes in proliferative T cell responses as well as increased expression of early and late T cell activation markers (3, 7, 9 -11). In addition, alterations in Th1 and/or Th2 lymphocyte function have been described (12)(13)(14)(15)(16), resulting in production of cytokines that up-regulate autoantibody production by B cells, promote immune complex formation, and increase the apoptotic load (17,18). The exact role that accessory cells might have in inducing abnormal T cell responses in SLE is unclear; however, different groups have proposed that T cell disturbances in SLE could be induced or promoted, at least in part, by alterations in dendritic cell (DC) phenotype and function, because these are key regulators of the immune system (19 -22).…”
mentioning
confidence: 99%
“…16,38 In addition, SLE patients have significant higher serum concentrations of IL-18. 16 From the SLE development, the deficiency in enhanced gene transcription will be beneficial for the individual, as elevated levels of the proinflammatory IL-18 protein mediate many of the acute and chronic inflammatory processes. Indeed, studies in anticytokine therapy including TNF, IL-6, IL-18 and IFN-g in SLE have become an important issue in preventing from tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report showed that haplotype-TAC at position À656, À607 and À137, respectively, would lead to low promoter activity compared with other haplotypes-GCG and TAG.23 This may answer why the ht2 (TAC) haplotype is less in SLE patients than in controls because elevated serum IL-18 of SLE patients are observed as compared with normal individuals. [11][12][13]16 However, no further information about ht4 (GAC) haplotype in promoter activity assay is available. We cannot exclude other polymorphism-like position at À656 which may also contribute to the transcriptional activity of IL-18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation